Strengthening the Contractual Framework to Address Collective Action Problems in Sovereign Debt Restructuring. (Policy Papers; Policy Paper, 2014)
This paper identifies contractual reforms designed to address collective action problems in sovereign debt restructuring. Since any decisions regarding the design of contractual provisions will need to be made by the sovereign issuer and its creditors, it is recognized that the Fund's primary role will be to facilitate agreement on the design and use of these provisions.